Perancangan Sistem Informasi Sekolah Berbasis WEB Menggunakan Metode Waterfall Pada SDN Bojongsari 4 - Rizky Trihandono, Muhammad; Chrisna Putra, Rangga; Lajaa, Widiya; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
This study aims to design a web-based school information system as a solution to the ineffective dissemination of academic information at SDN Bojongsari 4. The system development method used is the Waterfall model, which consists of requirement analysis, system design, coding, testing, implementation, and maintenance. Data collection was carried out through observation, interviews, and literature study. The result of this study is a web-based school information system with key features such as school profile, announcements, gallery, and academic information. The implementation of this system is expected to help the school manage and distribute information centrally and provide easy access for students, parents, teachers, and the general public. With this system, information delivery becomes more effective, efficient, and well-organized. Black Box testing shows that all system functions run as expected.